DEPLOYMENT OF SENSOR NETWORKS FOR EFFICIENT POWER CONSUMPTION MONITORING APPLICATION - Nazhatul Hafizah Kamarudin; Mohammad Arif Ilyas; Saidatul Izyanie Kamarudin; Marizuana Mat Daud, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
This paper presents a wireless monitoring system implemented using a wireless sensor network and the XCTU software. The existing monitoring systems for tracking alternating current utilization in various devices face limitations in terms of real-time data acquisition and seamless wireless transmission to a central computer for comprehensive analysis. This hinders the ability to accurately measure electric current consumption, impeding the development of efficient energy management strategies. Therefore, the primary focus of this monitoring system is to wirelessly track the utilization of alternating current in various devices. The wireless monitoring system relies on the integration of the XBEE device and the SCT 013 current sensor. The SCT 013 current sensor accurately measures electric current consumption, exhibiting a mere 0.03 variation, while the XBEE device is employed to transmit this data wirelessly to a computer for subsequent data analysis. In this configuration, the XBEE operates in AT mode for seamless data transfer to the computer.